2013
DOI: 10.1186/1472-6874-13-53
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for inter-generational Sex: a cross-sectional cluster survey of Barbadian females aged 15–19

Abstract: BackgroundThe aim of this study was to establish the prevalence and risk factors for intergenerational (IG)-sex in females aged 15–19 residing in Barbados.MethodsThis cross sectional cluster survey was conducted in a 2.6% national sample in the age range (n = 261) recruited from multiple polling districts chosen with a probability proportional to size. Consent was obtained from participants aged ≥18 years or from parents/guardians of participants <18 years, with participant assent. The prevalence of age at fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 39 publications
1
16
1
Order By: Relevance
“…Factors associated with early sexual debut have been identified as follows: not living with both biological parents (5), lack of parental monitoring (5) and connectedness (6), having more advanced physical maturity (5), having more permissive attitudes toward sex (5,7), alcohol use (5,8), sexual risk behaviour (1,9), unintended pregnancy (10), delinquency (5), violence (8), history of physical and sexual abuse (7), school problems (5) and (for girls) depressive symptoms (5).…”
Section: Introductionmentioning
confidence: 99%
“…Factors associated with early sexual debut have been identified as follows: not living with both biological parents (5), lack of parental monitoring (5) and connectedness (6), having more advanced physical maturity (5), having more permissive attitudes toward sex (5,7), alcohol use (5,8), sexual risk behaviour (1,9), unintended pregnancy (10), delinquency (5), violence (8), history of physical and sexual abuse (7), school problems (5) and (for girls) depressive symptoms (5).…”
Section: Introductionmentioning
confidence: 99%
“…The drivers of the epidemic in this population are thought to be complex and multi-layered and include early age of irst sexual activity, gender-based violence, cultural norms such as multiple concurrent partnerships and sex for money or favors, as well as the social exclusion of certain groups based on sexuality or sexual orientation. 17,[19][20][21] Studies from the Caribbean and those from the sub-Saharan Africa have shown that risk taking behaviors among the young adults, remain at the center of continuing spread of HIV [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Stage 1 -the selection of a 10% random sample of enumeration districts (EDs) or 60 EDs Stage 2 -the selection of twenty (20) households within each of the sixty (60) EDs Stage 3 -the random selection of a prospective respondent from each pre-selected household by interviewers using the Kish method.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…Number of non-marital sexual partners was coded as '0', '1' and '2+'. Men who engage in CGRs often engage in multiple partnering (Drakes et al, 2013;Odimegwu & Mutanda, 2017). Therefore, it was assumed that there was a higher likelihood of engaging in a CGR among men who also engaged in multiple partnering.…”
Section: Sexual Behaviour Variablesmentioning
confidence: 99%
“…Evidence shows that cross-generational relationships are characterized by transactional sex, as well as multiple partnering, as most of the men engaged in these relationships are already married with families of their own (Drakes et al, 2013). Older men often view these relationships more as a recreational pursuit than a long-term union that may lead to marriage (Kuate-Defo, 2004;Leclerc-Madlala, 2008;Ojebode et al, 2010Ojebode et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%